Competency Assessment in the Position of Police Personnel: Comparison of Several Countries - Aditya Hardyanto; Chairul Muriman Setyabudi; Vita Mayastinasari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The police have a duty to ensure the safety of all citizens. This needs to be done competently by each member of the police force based on the position he holds. Therefore, before occupying a position, it is necessary to assess whether a person is suitable and can carry out his duties in that position properly. Existing practice in several countries suggests different approaches to conducting competency assessments for this purpose. This paper aims to compare the competency assessment process as the basis for placement in several countries, namely the United States, England, Germany & France and Indonesia. The research was conducted using a literature study method and involved collecting data from various literature sources such as books, journals and relevant documents. Descriptive analysis was then used to describe the findings. The results showed that competency assessment in all countries was carried out to match competencies with vacant positions. Competency assessment in the United States is based on behavior, in England with a functional approach, in France and Germany with a multidimensional approach, while in Indonesia with an assessment center. The difference between Indonesia and other countries can be seen from the use of psychological tests and/or the involvement of psychological experts in the assessment process. In addition, in Indonesia the training is carried out before the assessment while in other countries the training is carried out after the assessment and before taking the position. This is ultimately expected to be able to provide personnel who work according to their positions and then improve the performance of the Police.